Homœopathic treatment of handicapped children - Haidvogl, M.; Lehner, E.; Resch, D.M. (British Homeopathic Journal, 1993)
40 children attending a nursery and school for the handicapped were seen in a total of 55 consultations. Following detailed case taking from parents and school staff, medicines were selected by computer repertorization and verified against the child's constitutional type. Outcome was assessed with reference to preselected target symptoms.18 of the 40 children responded well in all target symptoms, 11 showed improvement in some but not all target symptoms; 7 children did not respond to treatment, and in 4 outcome could not be assessed. Children with organic brain damage, autism and definite syndromes generally responded well; those whose handicap was due to social deprivation generally failed to respond. Major responses were increased drive and improvement in hyperactive and aggressive behaviour, which enabled the children to benefit more from their education. Physical symptoms and problems such as stammering and enuresis also improved.
Keywords: Mental handicap; Target symptoms; Behaviour; Organic brain syndromes; Down's syndrome; Social deprivation